2010
DOI: 10.1080/19440040903527368
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and classification of single kernel fluorescence hyperspectral data with aflatoxin concentration in corn kernels inoculated withAspergillus flavusspores

Abstract: The objective of this study was to examine the relationship between fluorescence emissions of corn kernels inoculated with Aspergillus flavus and aflatoxin contamination levels within the kernels. Aflatoxin contamination in corn has been a long-standing problem plaguing the grain industry with potentially devastating consequences to corn growers. In this study, aflatoxin-contaminated corn kernels were produced through artificial inoculation of corn ears in the field with toxigenic A. flavus spores. The kernel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 14 publications
5
61
0
Order By: Relevance
“…Application of HSI was done for food quality evaluation soybean seeds, wheat, barley grains and Portobello mushroom (Agaricus bisporu) (Taghizadeh et al, 2011, Tumuluru et al, 2010, Arngren et al, 2011, Huang et al, 2014a, 2014b and detection of defects in apple fruits and lettuce leaves (Baranowski et al, 2012, Simko et al, 2015. In parallel, experiments using HSI techniques for detection of fungal infections in fruits of citrus, leaves of sugar beet, wheat and maize have proven the applicability of the technique (Lorente et al, 2013, Mahlein et al, 2010Hillnhütter et al, 2011, Firrao et al, 2010Yao et al, 2010, Bauriegel and Herppich, 2014, Williams et al, 2012. Nowadays, HSI methodologies based on various indices have been mostly used for detection of photosynthetic pigments like chlorophylls, carotenoids as well as of the other major compounds in leaves and fruits, such as anthocyanins and flavonoids (Deepak et al, 2015;Matros and Mock, 2013, Hölscher et al, 2009, Zhao et al, 2005, Coops et al, 2003, Ferri et al, 2004.…”
Section: Hyperspectral Imaging and Its Utilization In Crop Phenotypinmentioning
confidence: 99%
“…Application of HSI was done for food quality evaluation soybean seeds, wheat, barley grains and Portobello mushroom (Agaricus bisporu) (Taghizadeh et al, 2011, Tumuluru et al, 2010, Arngren et al, 2011, Huang et al, 2014a, 2014b and detection of defects in apple fruits and lettuce leaves (Baranowski et al, 2012, Simko et al, 2015. In parallel, experiments using HSI techniques for detection of fungal infections in fruits of citrus, leaves of sugar beet, wheat and maize have proven the applicability of the technique (Lorente et al, 2013, Mahlein et al, 2010Hillnhütter et al, 2011, Firrao et al, 2010Yao et al, 2010, Bauriegel and Herppich, 2014, Williams et al, 2012. Nowadays, HSI methodologies based on various indices have been mostly used for detection of photosynthetic pigments like chlorophylls, carotenoids as well as of the other major compounds in leaves and fruits, such as anthocyanins and flavonoids (Deepak et al, 2015;Matros and Mock, 2013, Hölscher et al, 2009, Zhao et al, 2005, Coops et al, 2003, Ferri et al, 2004.…”
Section: Hyperspectral Imaging and Its Utilization In Crop Phenotypinmentioning
confidence: 99%
“…In a recent study [11], a fluorescence peak shift was discovered in aflatoxin contaminated corn kernels. This spectral feature indicates that the spectral angle change in contaminated corn kernels may be an area suitable for further exploration using the SAM algorithm.…”
Section: Introductionmentioning
confidence: 98%
“…For Brazil nuts, the hand picking segregation based on segregation of kernels with fluorescence has been used in Bolívia as an aflatoxin decontamination technique. Yao et al (2010) reported good correlation between single kernel fluorescence hyperspectral data and aflatoxin concentration in maize.…”
Section: Segregation By Appearance Featuresmentioning
confidence: 99%
“…Nowadays, BGYF is not currently used as a technique of decontamination of aflatoxin contaminated maize, it has been used as a technique for analyzing samples to detect aflatoxin contamination. Other types of fluorescence have been studied as a way to indicate contaminated peanuts, almonds, and maize (Pelletier & Reizner, 1992;Shade and King, 1984;Yao et al, 2010). A device capable of measuring fluorescence intensities from peanut surfaces and physically rejected peanuts having undesired fluorescence properties was described (Pelletier et al, 1991), however a comparison of the efficiency between it and the color sorting process in peanuts lots showed that it was not effective as an aflatoxin decontamination technique (Pelletier & Reizner, 1992).…”
Section: Segregation By Appearance Featuresmentioning
confidence: 99%